Using Parents as Peer Educators: Insights from a Community-Based Programme for Corporal Punishment Prevention - Ofoha, Dorothy; Saidu, Rosemary (NIU Journal of Humanities, 2021)
Despite the popularity of peer education as a method of delivering interventions in school settings, reports of its use with adults in local community settings are scarce. Thus, we present some insights on the implementation of a parenting education programme delivered to parents through peer education. The research presented in this paper is part of a larger, community-based, quasi-experimental, intervention study that was conducted to address a community-identified need to reduce parental corporal punishment practices. In that study, we developed and implemented an 8-week programme of intervention through a three-tiered train-the-trainer model in which we trained local community parents as parent peer educators (PPEs) to deliver the intervention to their peers. The effectiveness of the programme was tested and the results yielded many positive outcomes for the participating parents. In the current study, we focused on the PPEs to determine how well they had delivered the programme, in terms of adherence to programme curriculum and quality of delivery. The need for this assessment is warranted to see whether the intervention was implemented as intended, which would allow increased confidence in attributing the observed effects to the intervention. The data gathered through a fidelity measure indicated that the PPEs covered all 40 of the content areas of the programme and achieved a 93.3% measure of adherence, and demonstrated 80.0% fidelity in programme delivery. Findings showed that the intervention was delivered with high fidelity and that using parents as peer educators can be effective for corporal punishment prevention. Keywords: Parent peer education, community-based intervention, corporal punishment prevention, implementation fidelity